VIRTUAL TAFSIR OF INDONESIAN HABAIB: A CRITICAL DISCOURSE ANALYSIS OF YOUTUBE-BASED QUR’ĀNIC INTERPRETATION - Ubaidillah; Robitoh Widiastutik (UIN Raden Mas Said Surakarta, 2025)
This study examines the tafsir studies by Habib and Syarifah on YouTube with Norman Fairclough’s critical discourse analysis. The findings of discourse interpretation related to the production, dissemination, and consumption of discourse on Habib and Syarifah on social media explain that Habib Novel Alaydrus and Syarifah Halimah Halaydrus are YouTuber da’i who utilize the routine of studying majlis taklim, in contrast to Habib Ja’far’s YouTube content. The tafsir approach in this study emphasizes social and communal values (ādāb ijtimā‘ī) through a thematic tafsir method (mauḍū‘ī). Interestingly, Habib Novel tends to approach Tafsir through the stories of the prophets (qiṣṣatu al-anbiyā’). At the same time, Habib Ja’far relies on hadith narration (tafsīr bi al-riwāyah), and Halimah Alaydrus enhances the Tafsir with critical reasoning (tafsīr bi al-ra’yi). Habib Novel’s rhetorical approach is founded on an interpretative-textualist-dogmatic paradigm. Meanwhile, Habib Ja’far adheres to an interpretative-intertextualist critical paradigm, and Halimah Alaydrus employs an interpretative-textualist-critical paradigm. At the social context level, the focus shifts to fatalistic ideology, inclusive-dialogical approaches, and critical feminism. These significant findings can be utilized to advance tafsir studies within the context of a digital media society.